Convergence of Path and Approximation of Common Element of Null Spaces of Countably Infinite Family of m-Accretive Mappings in Uniformly Convex Banach Spaces - E. U. Ofoedu; Y. Shehu (International Journal of Mathematics and Mathematical Sciences)
We prove path convergence theorems and introduce a new iterative sequence for a countably infinite family of m-accretive mappings and prove strong convergence of the sequence to a common zero of these operators in uniformly convex real Banach space. Consequently, we obtain strong convergence theorems for a countably infinite family of pseudocontractive mappings. Our theorems extend and improve some important results which are announced recently by various authors.